2018
DOI: 10.1111/1365-2664.13090
|View full text |Cite
|
Sign up to set email alerts
|

Linking landscape composition to predator‐specific nest predation requires examining multiple landscape scales

Abstract: Landscape composition around bird nests can strongly influence nest predation, a major cause of reproductive failure for many species. Understanding this relationship may improve the effectiveness of management actions aimed at reducing predation. Despite attempts to link landscape composition to nest predation, consistent patterns have proven elusive, likely because studies often examine only one landscape scale, thereby overlooking scale‐specific interactions between predators and landscape features. To demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 73 publications
(163 reference statements)
2
40
0
7
Order By: Relevance
“…Evidence for adaptive habitat selection provides support for the theoretical model, suggesting that animals should possess the ability to accurately assess habitat quality (Fretwell & Lucas, 1970 (Chiavacci, Benson, & Ward, 2018;Ibáñez-Álamo et al, 2015;Ricklefs, 1969). In support of this, after placing nest cameras at select nests (n = 47) in 2015, we found that 80% of known nest failures were caused by predation, with 55% due to depredation by snakes, avian predators, and mammals.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Evidence for adaptive habitat selection provides support for the theoretical model, suggesting that animals should possess the ability to accurately assess habitat quality (Fretwell & Lucas, 1970 (Chiavacci, Benson, & Ward, 2018;Ibáñez-Álamo et al, 2015;Ricklefs, 1969). In support of this, after placing nest cameras at select nests (n = 47) in 2015, we found that 80% of known nest failures were caused by predation, with 55% due to depredation by snakes, avian predators, and mammals.…”
Section: Discussionsupporting
confidence: 58%
“…F I G U R E 3 Predicted daily survival rate and numbers of fledglings produced per nest and 95% confidence intervals of Bell's Vireo (BEVI) and Willow Flycatcher (WIFL) nests relative to % restored habitat within 1,200 m and % forest cover within 1,200 m of a nest, respectively important cause of avian nest failure (Chiavacci, Benson, & Ward, 2018;Ibáñez-Álamo et al, 2015;Ricklefs, 1969). In support of this, after placing nest cameras at select nests (n = 47) in 2015, we found that 80% of known nest failures were caused by predation, with 55% due to depredation by snakes, avian predators, and mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of a nest Although we were unable to identify specific nest predators, except for rare encounters during monitoring (e.g., an observed garter snake [Thamnophis spp.] blackbird nest depredation), a recent study using nest cameras in Illinois identified 9 bird, 13 mammal, and 5 snake species depredating bird nests, with raccoon, long-tailed weasel Mustela frenata, and fox snake Pantherophis vulpinus representing the highest portion of events in decreasing order (Chiavacci, 2016). Many of these predators were likely common nest predators in our study area.…”
Section: Nest Searching and Monitoringmentioning
confidence: 85%
“…Nevertheless, habitat management may be ineffectual under certain landscape and patch contexts which conservation organizations have less control over. Landscape-scale features are suspected to strongly affect the nest predator community, which for birds, is commonly the highest source of nest failure (Chiavacci, Benson, & Ward, 2017;Stephens, Koons, Rotella, & Willey, 2004). For grassland birds, forest edges seem to negatively impact nests because nest predators, such as raccoons (Procyon lotor), are more active around these edges (Barding & Nelson, 2008).…”
Section: Introductionmentioning
confidence: 99%